The research on the fixation strength of tapered cone bit teeth. (June 2021) - Yang, Yingxin; Song, Dongdong; Chen, Hanyu; Chen, Xin; Chen, Lian
Highlights: Design taper tooth for the failure of the tooth loss. A device is designed to study axial/ transverse loads on taper teeth at different taper. The taper, transverse load and interference magnitude contribute to failure. The taper tooth also solves the tooth dropping in high geothermal drilling. Abstract: In view of the tooth dropping phenomenon caused by the complex formation and other factors of the cone bit, a taper structure tooth is proposed. Experimental research on the strength of the proposed taper tooth was performed to study the influence of taper, interference, and transverse force on tooth fixation strength. The experimental results show that for different tapers (C50, C100, C200, C300, and C400), the maximum fastening force corresponds to an interference of 0.095 mm, and is 5.39–85.36% higher than that of a conventional cylindrical tooth, and the maximum fastening force is 30.25 kN for a C50 taper. Simulation results by the finite element method, were within 10% of the experimental results, verifying the simulation model. Through the numerical simulation of the tapered and cylindrical teeth at different temperatures, it is concluded that tapered teeth have better fixation strength than the cylindrical teeth, which can greatly improve the drilling efficiency of the cone bit in conventional and high-temperature drilling.